Partisipasi Masyarakat dalam Program Sabilulungan Kota Bandung: Studi Kasus Pengelolaan Bantuan Sosial Berbasis Digital - Kemitha, Metha Zahra; Mulyani, Safira Sri; Kurniawan, Sabilla Aulia Putri; Andhita, Sabrina Ratu; Andre Ariesmansyah (Universitas Pahlawan Tuanku Tambusai, 2025)
The Sabilulungan program, implemented by the Bandung City Government, is an effort to enhance transparency and public participation in the management of digital-based social assistance. This study aims to analyze how the public participates in this program and the factors that influence its success. Through a qualitative descriptive approach with literature study, this research finds that service quality and digital literacy are the main factors affecting public participation levels. Additionally, the active role of the government in providing education and outreach related to technology usage is key to improving public understanding. The findings suggest that although Sabilulungan provides significant opportunities for public involvement, challenges related to service quality and technology comprehension still require further attention. This study recommends improving the service quality of the digital platform and increasing digital literacy outreach to expand public participation.